Foreign Words and Phrases in Newspaper Film Reviews - Vardanyan, Irina (Armenian Folia Anglistika, 2010)
The article provides a thorough analysis of the role of foreign words and phrases in newspaper film reviews. They bring expressiveness to newspaper film reviews making them more impressive. Foreign words and phrases fulfil the functions of communication and that of impact. The frequency of their use is conditioned by the social and educational level of the reader.